Health Retention: Health Regulations and Archive Management - Lilik Afifah; Rokhman Handoyo; Kalia Labitta Putri Alivia (PT FORMOSA CENDEKIA GLOBAL, 2024)
Medical records are documents containing patient identification data, examinations, treatments, actions, and other services provided to patients. The storage of medical records, which includes the creation and archiving of medical information, is considered crucial for improving service quality. In managing medical records, the destruction of medical records becomes one of the most important elements. Conventional medical record files are no longer efficient to use; therefore, the destruction of these medical record files is necessary. This study aims to analyze the legal aspects of destroying conventional medical record files in accordance with applicable regulations. The method used is descriptive qualitative with a normative legal research type, referring to the applicable regulatory approach. Results: Retention implementation according to health regulations and archive management still needs to be carried out to prevent accumulation and improve the quality of health services in hospitals. Conclusion: In the health ministerial regulations, laws, and archive regulations, there is an emphasis on the storage of medical records up to the retention activities. However, regulations regarding the retention of conventional medical record files are still limited or not detailed in the current regulations. Therefore, a clearer and more explicit regulation related to the retention or destruction of conventional medical records and their legal protection is needed.